Computational study for microwave pasteurization of beer and hypothetical continuous flow system design. (January 2022) - Karatas, Ozan; Topcam, Huseyin; Altin, Ozan; Erdogdu, Ferruh
Abstract: Beer pasteurization is carried out in conventional systems where low temperature and long time process (56 min process with 13 min pre-heating, 14 min heating, 6 min holding time and 23 min cooling time) is applied for bottled or canned products. Longer process times lead to losses in the sensory properties. Another approach is flash pasteurization where the beer is first pasteurized and then filled into bottles or cans. For flash pasteurization, microwave (MW) process with rapid heating feature might be an innovative alternative. Therefore, the objective of this study was to explore the MW processing for beer pasteurization. For this purpose, a computational mathematical model was developed to determine the temperature change of beer during MW process and experimentally validated in a 2450 MHz lab-scale system. Following the validation, process design studies for a continuous flow system were carried out. These studies demonstrated the MW application as a rapid process (e.g. 60 s of total MW heating time at 5000 W with a short holding time of 27 s) to achieve the required pasteurization unit at a flow rate of 50.4 kg/h. This confirmed the MW process as a possible industrial application. Using these results, continuous flow process optimization studies for industrial process considerations might be planned. Highlights: Microwave pasteurization of beer by computational modeling was investigated. Continuous flow microwave pasteurization was confirmed using the validated model. Design considerations for hypothetical continuous flow systems were presented. Significant time reduction compared to conventional processes were confirmed.